Linking patient-reported oral and general health-related quality of life - Paulson, Danna R.; Chanthavisouk, Phonsuda; John, Mike T.; Feuerstahler, Leah; Chen, Xing; Ingleshwar, Aparna (PeerJ, 2024)
Background The relationship between oral and overall health is of interest to health care professionals and patients alike. This study investigated the correlation between oral health-related quality of life (OHRQoL) and health-related quality of life (HRQoL) in a general adult population. Methods This cross-sectional study used a convenience sample of adult participants (N = 607) attending the 2022 Minnesota County and State fairs in USA, the 5-item Oral Health Impact Profile (OHIP-5) assessed OHRQoL, and the 10-item PROMIS v.1.2 Global Health Instrument assessed HRQoL. Spearman and Pearson correlations were used to summarize the bivariable relationship between OHRQoL and HRQoL (both physical and mental health dimensions). A structural equation model determined OHRQoL-HRQoL correlations (r). Correlations’ magnitude was interpreted according to Cohen’s guidelines (r = 0.10, 0.30, and 0.50 to demarcate “small,” “medium,” and “large” effects, respectively). Results OHRQoL and HRQoL correlated with r = 0.52 (95% confidence interval, CI: [0.50–0.55]), indicating that the two constructs shared 27% of their information. According to Cohen, this was a “large” effect. OHRQoL, and the physical and mental HRQoL dimensions correlated with r = 0.55 (95% CI: [0.50–0.59]) and r = 0.43 (95% CI: [0.40–0.46]), respectively, indicating a “large” and a “medium” effect. OHRQoL and HRQoL were substantially correlated in an adult population. Conclusion Using OHIP-5 to assess their dental patients’ oral health impact allows dental professionals to gain insights into patients’ overall health-related wellbeing.
Keywords: Oral health-related quality of life; Health-related quality of life; Association; Correlation; Questionnaire; Oral health impact profile; OHIP-5; PROMIS